The Influence of APE on the Emotional Development of Early Childhood - Abelia Khoerunnisa; Dea Amelia; Hanifa Shofuroh (STIT Attaqwa, 2024)
Educational game tool is an object that can support the development of children, one of which is the social emotional development of children. Social and emotional development is an early stage in emerging abilities from zero to five years of age. The purpose of this study is how the teacher's strategy with the use of educational games in improving the social emotional development of children. In this study using qualitative methods with the approach of literature studies and data sources collected from scientific articles, theses, books, and theses. Based on the results of the study it can be concluded that educational game tools are very influential in supporting the social emotional development of children, and optimization of teacher strategies in the use of educational game tools.